2022
DOI: 10.1177/00194662221139364
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Fiscal Variables in Inf lation Variations in Sri Lanka

Abstract: Although the monetary policy impact on inflation is deliberated intensively in economic literature, the fiscal policy impact has not gained much interest, particularly in the developing countries. The later issue is theorised as the fiscal theory of price level. This article examines the potency of fiscal factors relative to the money growth in inflation in Sri Lanka for an extended period 1965–2018, and also for the post-reform period 1977–2018. The inflationary impacts of public debt, budget deficit and publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This finding is consistent with the submission of the IMF and the World Bank that warned that following the rise in public debts, an inflation rate of more than 12% is expected for SSA. The result is also supported by Maitra and Mondal ( 2022 ) who investigated the inflationary impacts of public debt, budget deficit and public expenditure for Sri Lanka, and found that fiscal policy instruments are, in general, inflationary.…”
Section: Empirical Analysis and Discussion Of Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…This finding is consistent with the submission of the IMF and the World Bank that warned that following the rise in public debts, an inflation rate of more than 12% is expected for SSA. The result is also supported by Maitra and Mondal ( 2022 ) who investigated the inflationary impacts of public debt, budget deficit and public expenditure for Sri Lanka, and found that fiscal policy instruments are, in general, inflationary.…”
Section: Empirical Analysis and Discussion Of Resultssupporting
confidence: 59%
“…Consequently, some scholars (see Akanbi 2015 ; Klein and Linnemann 2020 ; Ferrara et al 2021 ; Olaoye 2022 ; Hole 2022 ; Boesler 2022 ; Maitra and Mondal 2022 ) have investigated the effect of fiscal policy on inflation in both developed and developing economies (see Table 1 for summary of literature).…”
Section: Introductionmentioning
confidence: 99%
“…Fiscal policy instruments used in the past in Sri Lanka have been ineffective, influenced by imprudent decisions that have led to lower productivity, such as overstaffing in the public sector, increasing expenditures, and lower accountability on financial management, outputs, and outcomes of public expenditures (Velnampy and Achchuthan, 2013) [27]. These expenditures have contributed to inflation because they added little to GDP (Maitra et al, 2022) [28]. Decreasing spending is not a politically popular option in a democracy such as Sri Lanka, which has periodic elections in which voter resentment can dislodge lawmakers from holding office.…”
Section: Relevant Literature 21 Fiscal Policymentioning
confidence: 99%